Immanuel Kant’s idea of radical evil as a systematic and terminological problem - Anna Szyrwińska-Hörig (Ethic@: an International Journal for Moral Philosophy, 2023)
The paper investigates the systematic connection between Kantian concept of radical evil and radical indeterministic idea of freedom. According to the presented thesis the systematically relevant interpretation of the radical evil concept requires considering not only philosophical ideas Kant`s but also the historic background in which they were formulated. Particularly the specific situation of German philosophic terminology in the 17th and early 18th Century will be acknowledged as one of the most significant factors influencing the development of the radical evil concept. For the sake of methodological precision of the presented analysis, the differentiation between thick and thin concept of evil will be introduced.